A new somasteroid from the Fezouata Lagerstätte in Morocco and the Early Ordovician origin of Asterozoa. (27th January 2021) - Hunter, Aaron W.; Ortega-Hernández, Javier
Abstract : The somasteroids are Lower Palaeozoic star-shaped animals widely regarded as ancestors of Asterozoa, the group of echinoderms that includes brittle stars and starfish. However, the origin of asterozoans, the assembly of their distinctive body organization, and their relationships with other Cambrian and Ordovician echinoderms remain problematic owing to the difficulties of comparing the endoskeleton between disparate groups. Here, we describe the new somasteroid Cantabrigiaster fezouataensis, a primitive asterozoan from the Early Ordovician Fezouata Lagerstätte in Morocco. Cantabrigiaster shares with other somasteroids a unique endoskeletal arm organization and the presence of rod-like virgal ossicles that articulate with the ambulacrals, but differs from all other known asterozoans in the absence of adambulacral ossicles defining the arm margins, evoking parallels with non-asterozoan echinoderms. Developmentally informed Bayesian and parsimony phylogenetic analyses, which reflect the homology of the biserial ambulacral ossicles in Palaeozoic echinoderms according to the extraxial–axial theory, recover Cantabrigiaster as the earliest divergent stem-group asterozoan. Our results illuminate the ancestral morphology of Asterozoa, and clarify the affinities of problematic Ordovician Asterozoa. Bayesian inference and parsimony demonstrate that somasteroids represent a paraphyletic grade within stem- and crown-group Asterozoa, whereas stenuroids are paraphyletic within stem-group Ophiuroidea. Our results also offer potential insights on the evolutionary relationships between asterozoans, crinoids and potential Cambrian stem-group representatives.